Correlation between the dielectric and electrochemical properties of TiO2-V2O5 nanocomposite for energy storage application. (10th March 2018) - Ray, Apurba; Roy, Atanu; Bhattacharjee, Swarupananda; Jana, Srikanta; Ghosh, Chandan Kumar; Sinha, Chittaranjan; Das, Sachindranath
Abstract: The structural and morphological analysis of TiO2 -V2 O5 nanocomposite has been performed using FTIR, XRD and FESEM. Temperature (300 K-500 K) and frequency dependent dielectric properties and complex impedance analysis have been carried out to investigate the effect of grain and grain boundary of the synthesized sample. The electrochemical properties like cyclic voltammetry (CV), galvanostatic charge/discharge (GCD) rate and electrochemical impedance (EIS) of the electrode material have also been investigated. The maximum specific capacitance (Cm ) obtained from cyclic voltammetry (CV) and GCD measurement are 262 Fg -1 at scan rate 2 mV s −1 and 251.5 Fg -1 at current density 0.09 mA cm −2 respectively. The stability of the electrode material is measured up to 1000 cycles. The correlation between the dielectric properties and electrochemical properties is successfully demonstrated for the first time. Large grain boundary resistance played an important role for low specific capacitance value at room temperature.